Investigation of ground motion vertical and horizontal component effects on the IDA curves for the regular and irregular steel moment frames - mehrdad talebzade zaviyeh (Iranian Society of Structrual Engineering (ISSE), 2019)
The effect of seismic vertical components on the seismic behavior of structural systems can be considerable. The vertical component of ground motion records can cause the brittle collapse of columns resulting in global collapse of structures. This effect is more crucial for near fault ground motions with larger vertical accelerations. Nevertheless, the effect of seismic vertical excitations is neglected in time-history analysis procedures on common structural systems. This may results in unconservative results in dynamic analyses. Therefore, it is very important to evaluate the damaging effects of vertical component of seismic excitations. In this paper, the effect of vertical excitations on the seismic response of steel moment frames with regular and irregular configurations along the height. Incremental dynamic analysis is employed to consider the effect of seismic excitations with various intensities. In IDA analysis, the seismic loads are applied to the structures with increasing intensities. In this paper, the seismic loads are applied to the structures in two manners, once considering only the horizontal component and secondly considering vertical and horizontal components simultaneously. The IDA curves are compared for two cases to find the effect of vertical excitations on global seismic demands. Also, the evaluations are made separately for regular and irregular frames to find the effect of vertical irregularity. The observed results revealed that the vertical components may increase the nonlinear displacements, especially for large intensities. The investigations demonstrate that the increase of column axial forces causes brittle buckling of columns and expedites the formation of plastic hinges leading to global collapse of structure. In irregular frames with soft stories, the buckling of slender columns is more crucial than regular structures. Therefore, it is suggested that the vertical components are considered for analyzing steel moment frame structures against near fault ground motions